Genetic analysis in European ancestry individuals identifies 517 loci associated with liver enzymes - Raha Pazoki (Nature Portfolio, 2021)
Plasma levels of liver enzymes provide insights into hepatic function and related diseases. Here, the authors perform a genome-wide association study on three liver enzymes, identifying genetic variants associated with their plasma concentration as well as links to metabolic and cardiovascular diseases.